Role of Irrigation in Crop Production and Productivity: A Comparative Study of Tube Well and Canal Irrigation in Shreepur VDC of Kanchanpur District - Paudyal, Narayan Prasad (Geographical Journal of Nepal, 2011)
The main purpose of the study is to find out the changes in production and productivity and the living standard of the people in Shreepur VDC after the introduction of canal and tube well irrigation facility. The prime issue related to the study is whether the canal and tube well irrigation facility has brought changes in crop production and productivity and contributed to improving the living standard of the people in the study area. The researcher took the sample of 113 households out of the total 750 households in the VDC using simple random sampling procedure. The informants were interviewed with the help of questionnaires. Similarly the informants were observed using participatory observation method. It is found that there have been changes in production and productivity after the provision of irrigation facility. Most of the baries (non-irrigable land) where maize, mustard and gram were grown have been utilized to grow paddy and wheat like in khets (irrigated). Paddy production has increased by 68.75 percent and wheat production has increased by 193.0 percent. Living standard in terms of house type, type of toilet, use of pure drinking water, use of consumer accessories has also been improved. The Geographical Journal of Nepal, Vol. 8, 2010-2011: 53-62